KERENTANAN DAN TANTANGAN KESEJAHTERAAN PENGEMUDI GRAB DALAM EKONOMI GIG INDONESIA - Al-fadani, Syauqi Raihan; Nurdin, Nurdin (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2025)
Abstract. The purpose of this study is to explain the conflict of social welfare policies between online motorcycle taxi drivers, PT. Grab Indonesia and the Government. This study uses a qualitative method to explain the dynamics and power relations between the Grab online motorcycle taxi driver group, the Ministry of Digital Communication of the Republic of Indonesia, and PT. Grab Indonesia regarding demands for social welfare. Data collection was carried out through in-depth interviews, literature reviews and observations. Meanwhile, the analysis of research problems was answered using social welfare theory and the concept of the gig economy. The results of this study explain that the power relations in determining the social welfare of gig workers are still dominated by the gig company Grab Indonesia. The weak position of the government has had implications for obstacles in making gig economy policies in the transportation sector to date. This condition has affected the level of social welfare of Grab online motorcycle taxi drivers which is not yet adequate. The low level of welfare of online motorcycle taxi drivers can be measured by low daily income, high workload, and the unavailability of health insurance facilities. In addition, the weak involvement of the government in regulating gig worker policies in Indonesia has also affected the political uncertainty of the social welfare of online motorcycle taxi drivers in general and Grab Indonesia online motorcycle taxi drivers in particular in the future amidst competition and scarcity of jobs in Indonesia.  Keyword: GIG Economy, Policy Conflict, GrabBike Drivers, Government, PT. Grab Indonesia.  Abstrak. Tujuan penelitian ini adalah untuk menjelaskan konflik kebijakan kesejahteraan sosial antara pengemudi ojek daring, PT. Grab Indonesia dan Pemerintah. Penelitian ini menggunakan metode kualitatif untuk menjelaskan dinamika dan relasi kekuasaan antara kelompok pengemudi ojek daring Grab, Kementerian Komunikasi Digital Republik Indonesia, dan PT. Grab Indonesia terkait tuntutan kesejahteraan sosial.  Pengumpulan data dilakukan melalui wawancara mendalam, kajian kepustakaan dan observasi. Sementara analisis permasalahan penelitian dijawab dengan menggunakan teori kesejahteraan sosial dan konsep ekonomi gig. Hasil dari penelitian ini menjelaskan bahwa relasi kekuasaan dalam menentukan kesejahteraan sosial pekerja gig masih didominasi oleh perusahaan gig Grab Indonesia. Posisi pemerintah yang lemah telah berimplikasi pada hambatan dalam pembuatan kebijakan ekonomi gig di bidang transportasi hingga saat ini. Kondisi ini telah mempengaruhi tingkat kesejahteraan sosial pengemudi ojek daring Grab yang belum layak. Rendahnya tingkat kesejahteraan pengemudi ojek daring dapat diukur dari pendapatan harian yang rendah, tingginya beban kerja, dan ketidaktersediaan fasilitas asuransi kesehatan. Selain itu masih lemahnya keterlibatan pemerintah dalam pengaturan kebijakan buruh gig di Indonesia juga telah mempengaruhi ketidakpastian politik kesejahteraan sosial pengemudi ojek daring umumnya dan khususnya pengemudi ojek daring Grab Indoenesia di masa mendatang di tengah kompetisi dan kelangkaan lapangan pekerjaan di Indonesia.   Kata Kunci:  Ekonomi GIG, Konflik Kebijakan, Pengemudi GrabBike, Pemerintah, PT. Grab Indonesia